LEFLUNOMIDE IN COMPLEX THERAPY OF JUVENILE RHEUMATOID ARTHRITIS - M.N. Nikolaeva; E.S. Zholobova; I.E. Shakhbazyan; V.Ya. El'yashevich ("Paediatrician" Publishers LLC, 2008)
The results of retrospective study of children with juvenile rheumatoid arthritis (JRA), torpid to standard antirheumatic therapy, treated with leflunomide (arava) as basis medication, are presented in this article. An effectiveness and safety of leflunomide in complex treatment of JRA was shown. Treatment with leflunomide results in remission and decrease of dose of peroral corticosteroids.Key words: children, juvenile rheumatoid arthritis, leflunomide.